A study on employees’ perception towards women leadership / Yasmira Yasin and Farah Fatin Mazlan - Yasin, Yasmira; Mazlan, Farah Fatin (Faculty of Administrative Science and Policy Studies, 2013)
Our Research project paper title is ‘A study on employees’ perception towards women leadership’. The study topic been chosen due to the issue arise such poor judgment women leader where people are not believes on their capabilities in administration such lack of commitment to lead employees and organization and also have lower level of self confidence. The objective of this research is to determine among the four factors; communication, usage of power, decision making and personal character, which is the most contribute to employees’ perception towards women leadership. Recommendations are suggested in order for women leaders may improve themselves in influenced their employees’ perception.The target population in this study comprises of the employees’ in Malacca Historic City Council (MBMB) whose work under a women leader. From 14 departments there are only 9 departments that have women as a top leader and the total population on this study was 353 employees’. By using the sampling technique of Disproportionate Stratified Sampling, the sample size for this study was only 181 employees’ as the respondents. Data been analyzed using the statistical correlations between measured variables.